Book-Tasting Presentations within an Early Childhood Educator Preparation Program - Johannah D Baugher; Narges Sareh (The Advocate, 2023)
This manuscript discusses a teacher education experience utilized within an early childhood literacy methods course named, book-tasting presentation. Existing literature suggests that book-tastings, in a variety of forms, are evident at the PK-12 level, yet not prevalent in higher education and specifically, teacher education. The aim of the book-tasting presentations is to expose early childhood teacher candidates to diverse, high-quality picturebooks and their application in early childhood settings to cook up a love of literacy among our youngest readers. This is achieved through the Experiential Learning Cycle as teacher candidates are tasked to experience, reflect, think, and act throughout this exercise. Facilitated in a conducive, academic environment with access to rich, instructional materials and intentional, learning experiences, teacher candidates have authentic opportunities to reflect on their professional practice regarding the use of picturebooks in early childhood settings.
Keywords: early literacy; teacher education; picturebooks; early childhood education; higher education